Evolution of policies affecting land settlement schemes in Malaysia - Samaruddin Rejab, (Universiti Kebangsaan Malaysia, 1978)
The aim of this article is to trace the evolution of policies affecting land Settlement Schemes. Special reference is given to four major periods of Malaysia's history: the Pre-Independent Period (1945-1957); the Malayan Period (1957-1963); the Early Malaysian Period (1963-1970); and the current New Economic Policy. Changes occur due to the nature of implementation, national political needs and practical considerations on the strategy and scope of the Project.